Inovasi Pelayanan Publik Pada Aplikasi Silacak (Sistem Informasi Lacak Armada) Dalam Upaya Peningkatan Layanan Pengangkutan Sampah Di Kantor Dinas Lingkungan Hidup Kota Tangaerang - Bella Nur Hidayah; Agus Suherman; Muhammad Ibrahim Rantau (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2025)
Public services are basically closely related to various social aspects of state life. The government is tasked with providing various public services needed by society in various fields such as education, health and information technology. Currently, Tangerang City has a population of 2,953.85 people, and in a day the waste production of the people of Tangerang City amounts to 1,300 tons per day. One of the efforts to improve public services in Tangerang City is through electronic-based public service innovations carried out in Tangerang City. Tangerang City created a website-based application public service, namely SILACAK (Fleet Tracking Information System). The aim is to find out the implementation of waste transportation services before the SILACAK Application (Fleet Tracking Information System) and after the SILACAK (Fleet Tracking Information System) Application in Public Service Innovation in the SILACAK Application (Fleet Tracking Information System) at the Tangerang City Environmental Service Office. This research uses a type of qualitative research which has descriptive characteristics. The SILACAK Application Waste Transportation Service has received a lot of appreciation from all levels of society who need government assistance for waste transportation and the application or innovation presented by the government is really enjoyed and benefits many people, both from government institutions themselves and non-government .